Food waste minimisation practices - M.A. Elmesh, Ahmed; Mohd Yasin, Nurain Izatti; Suhadi, Aznin Syazana; Abu Hasan, Wan Hasila; Munir, Siti Nur Ummiah; Md. Zainuddin, Nurul Sri Arty Arfeeqa (Penerbit UTHM, 2020)
In order to achieve an efficient waste minimisation, there is a need to be an understanding on the awareness of the waste minimisation in the major food operator including cafeteria. Thus, this chapter provide an observation of the waste minimisation at several cafeterias which include of manageable and unmanageable waste systems. This chapter will explain how the cafeteria is doing to cut back on or at least recycle the huge amount of food waste or cooking waste for waste minimization. Case studies were conducted at the Sis Wani House of Catering, Enayati Cafeteria and Hadramawt Cafeteria in UTHM campus. Determination of the level of knowledge about waste minimization among cafeteria workers and customers (students) were studied to measure the awareness on waste minimization.